A Comparative Analysis of Consumer Preferences and Brand Perception Between Pepsin and Coco-cola in Ahmedabad and Mumbai - kuhada, Vashishth; Vidani, Jignesh; Katariya, Krutika (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study offers a thorough analysis of the consulting services provided by Head Quest HR Solutions LLP, a reputable Ahmedabad-based HR consulting firm. The study's objectives are to investigate the range of services offered, the technologies employed, and how well these services enhance organizational performance. Using a mixed-methods approach, this study integrates qualitative data from semi-structured interviews with important stakeholders with quantitative data from structured customer surveys. Research indicates that Head Quest HR Solutions LLP employs a number of strategies that are tailored to the unique requirements of its customers. These methods improve overall organizational development, talent management, and employee engagement.In addition to offering useful information on HR consulting best practices, this study makes recommendations for enhancing the efficacy and efficiency of consulting services